2012
DOI: 10.1111/cpf.12010
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of dynamic contrast‐enhanced CT and MR imaging‐derived measurements in patients with cervical cancer

Abstract: This work is to compare the kinetic parameters derived from the DCE-CT and -MR data of a group of 37 patients with cervical cancer. The modified Tofts model and the reference tissue method were applied to estimate kinetic parameters. In the MR kinetic analyses using the modified Tofts model for each patient data set, both the arterial input function (AIF) measured from DCE-MR images and a population-averaged AIF from the literature were applied to the analyses, while the measured AIF was used for the CT kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…While the simple down-sampling method showed greater APD values (42.85% and 36.06% on average) in SD and range of K trans , the proposed method was able to reduce the corresponding APDs to 19.18% and 19.91% on average, respectively. Considering the good agreement in tumor perfusion and kinetic parameter estimates between DCE-CT and DCE-MRI studies reported by a number of papers, [45][46][47][48] one may find that the level of the APDs would be adequate for the application of the proposed method to a DCE-CT study to predict early treatment response in a similar setting.…”
Section: Discussionmentioning
confidence: 90%
“…While the simple down-sampling method showed greater APD values (42.85% and 36.06% on average) in SD and range of K trans , the proposed method was able to reduce the corresponding APDs to 19.18% and 19.91% on average, respectively. Considering the good agreement in tumor perfusion and kinetic parameter estimates between DCE-CT and DCE-MRI studies reported by a number of papers, [45][46][47][48] one may find that the level of the APDs would be adequate for the application of the proposed method to a DCE-CT study to predict early treatment response in a similar setting.…”
Section: Discussionmentioning
confidence: 90%
“…Still, studies have shown that ‘first pass’ DCE images after administration of contrast agent reflect tumor blood flow [ 107 , 110 ]. In addition, different dynamic imaging principles such as MRI, CT, and PET may provide similar estimates of flow-related tumor parameters, as long as proper image acquisition and quantification protocols are followed [ 93 , 94 , 111 , 112 ]. Thus, to identify regional flow–metabolism mismatch, one may combine DCE-MRI or DCE-CT with 18F-FDG PET, or perform full dynamic 18F-FDG PET.…”
Section: Discussionmentioning
confidence: 99%
“…The AIF CT was chosen in the internal carotid artery for DCE-CT and compared with VIF CT in the sagittal sinus. For this study, a population-based input function (AIF MRI ) was used for DCE-MRI analysis because of variability in the flip angle between patients ( 26 ) and it allowed for a robust comparison of the impact of the analysis methodology against DCE-CT ( 27 ). A 3D voxel mask, as well as a separate sum of squared errors mask, was created for each functional parameter to show the quality of fit of the transport model.…”
Section: Methodsmentioning
confidence: 99%